1996
DOI: 10.1093/oxfordjournals.humrep.a019021
|View full text |Cite
|
Sign up to set email alerts
|

Human Fallopian tubal epithelial cells in vitro:establishment of polarity and potential role of intracellular calcium and extracellular ATP in fluid secretion

Abstract: A pure population of human Fallopian tubal epithelial cells has been isolated by enzyme digestion, grown in primary culture and used to explore the biochemical basis of oviduct fluid secretion. Confluence was achieved in 3-7 days. Immunocytochemical labelling for cytokeratins indicated that the cells were epithelial in nature and formed extensive desmosomal contacts, producing a polarized layer in culture. By growing the cells on collagen-impregnated filters, a small transepithelial electrical potential differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Of particular relevance to the present report, ATP has been reported transiently to stimulate I sc or V te across cultures of bovine, mouse, and human oviductal epithelium (8,9,19,21), and we have earlier shown that ATP stimulates I sc across cultures of monkey oviductal epithelium with not only a transient but also a sustained response (26). Conversion of CO 2 to HCO 3 Ϫ by carbonic anhydrase constitutes an important step in HCO 3 Ϫ secretion across many epithelia (6,15,16,31), and we therefore tested the effects of acetazolamide on the response to ATP.…”
Section: Discussionmentioning
confidence: 65%
“…Of particular relevance to the present report, ATP has been reported transiently to stimulate I sc or V te across cultures of bovine, mouse, and human oviductal epithelium (8,9,19,21), and we have earlier shown that ATP stimulates I sc across cultures of monkey oviductal epithelium with not only a transient but also a sustained response (26). Conversion of CO 2 to HCO 3 Ϫ by carbonic anhydrase constitutes an important step in HCO 3 Ϫ secretion across many epithelia (6,15,16,31), and we therefore tested the effects of acetazolamide on the response to ATP.…”
Section: Discussionmentioning
confidence: 65%
“…Bovine oviducts at various stages of the estrous cycle were removed from cattle at a local abattoir within 5 min of slaughter. Epithelial cells were isolated according to the methods previously described for the isolation of rat uterine epithelium (15,18). The oviducts were immediately separated from connective tissue, fat, and major blood vessels, and the fimbriae were removed.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting luminal accumulation of sodium chloride generates an osmotic gradient pulling water into the lumen. In the oviduct, fluid secretion has been shown to be directly associated with chloride secretion (14,15). Oviduct fluid formation is essential to hydrate and protect the mucosal surface and to provide an appropriate ionic environment to facilitate healthy reproductive processes (25).…”
mentioning
confidence: 99%
“…The effect was mediated by activation of P2Y 2 or possibly P2Y 4 receptors (Cox and Leese, 1994;Villalon et al, 1995) located on the basal surface of the cells; it involved a rapid increase in Ca 2+ i due to Ca 2+ mobilization (Cox and Leese, 1994;Villalon et al, 1995;Dickens et al, 1996;Anon. ;Squires et al, 1995;Tiemann et al, 1996) and activation of Ca 2+ -dependent, apaminsensitive K + conductance (Keating and Quinlan, 2012).…”
Section: Fallopian Tubementioning
confidence: 99%